Effect of sustainable leadership practices on employee well-being at tour operators: The mediating role of job satisfaction - Ayad, Tamer Hamdy; Dwedar, Miral Ahmed; Elrayah, Musaddag (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to explore how sustainable leadership practices affect employee well-being at tour operators in Saudi Arabia and Egypt’s tourism context. It attempts to tackle issues such as those listed in the Sustainable Development Goals (SDGs) of the UN. Additionally, it seeks to understand the mediating role of job satisfaction between the study’s two main variables. Data were collected from 453 employees at tour operators in Saudi Arabia and Egypt and analyzed using descriptive statistics in Excel and SPSS, while PLS-SEM was employed to assess direct and indirect relationships between variables and test research hypotheses. The findings uncovered significant positive direct relationships between all sustainable leadership practices factors and employee well-being factors. Moreover, the study revealed that job satisfaction acts as a mediator in all direct relationships. These findings offer valuable insights for decision-makers at tour operators, enabling them to create an environment where employees feel valued, empowered, and aligned with the company’s core values. Furthermore, it provides a helping hand to build a resilient, engaged, and loyal workforce.